Faktor Faktor yang Mempengaruhi Masyarakat Tidak Mematuhi Protokol Kesehatan di Masa Pandemi Covid-19 - Asep Koswara; Adisel Adisel (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the factors that influence people not to comply with health protocols during the Covid-19 pandemic. This study uses a descriptive qualitative approach, namely the data collection techniques used in this study are the methods of observation, interviews and documentation. The results of this study prove that there are two factors that influence people not to comply with health protocols during the Covid-19 pandemic, including internal factors and external factors. Internal factors are factors that arise due to the influence or stimulation of the individual himself. Internal factors include age and habit factors. Then external factors, external factors are all factors that come from outside or all influences that come from outside. External factors include educational factors and economic or employment factors. The conclusions of this study indicate that there are two factors that can affect the community for not complying with the health protocol during the Covid-19 pandemic, namely internal factors and external factors. Keywords: Community Compliance, Covid-19 Pandemi, Health Protokol.